2002
DOI: 10.1079/bjn2001462
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofn-3 fatty acid supplemented parenteral nutrition on haemostasis patterns after major abdominal surgery

Abstract: In various diseases n-3 fatty acids exert anti-inflammatory properties. These effects seem to be related to the uptake and incorporation of eicosapentaenoic acid (EPA) into the cellular substrate pool after dietary intake of EPA, which is contained in fish oils (FO). In the state of inflammation EPA is released to compete with arachidonic acid (AA) for metabolism at the cyclo-oxygenase and the 5-lipoxygenase level. The metabolites of EPA have less inflammatory and chemotactic potency than the substances derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 30 publications
1
57
1
7
Order By: Relevance
“…Several studies have shown the mechanisms by which genes may influence the metabolism of nutrients, as well as the mechanisms by which nutrients can influence gene expression (Simopoulos et al 2008, Paolini-Giacobini et al 2003, Calder 2007. With advances in science, and emphasis on the study of nutrigenomics and nutrigenetics, it has been shown that certain nutrients can influence the inflammatory response, accelerating or regressing the development of many diseases (Heller et al 2002, Weiss et al 2002, Mayer et al 2003, Paolini-Giacobini et al 2003, Simopoulos et al 2008. Stern et al (2009), from the Singapore Chinese Health Study, through analyses taking into account variants in genes that are relevant for the proposed PUFAs mechanism of actionhypothesised that the genes which play key roles in the pathways that repair PUFA-induced damage might modify the effect of these FA on colorectal cancer.…”
Section: Polymorphismsmentioning
confidence: 99%
“…Several studies have shown the mechanisms by which genes may influence the metabolism of nutrients, as well as the mechanisms by which nutrients can influence gene expression (Simopoulos et al 2008, Paolini-Giacobini et al 2003, Calder 2007. With advances in science, and emphasis on the study of nutrigenomics and nutrigenetics, it has been shown that certain nutrients can influence the inflammatory response, accelerating or regressing the development of many diseases (Heller et al 2002, Weiss et al 2002, Mayer et al 2003, Paolini-Giacobini et al 2003, Simopoulos et al 2008. Stern et al (2009), from the Singapore Chinese Health Study, through analyses taking into account variants in genes that are relevant for the proposed PUFAs mechanism of actionhypothesised that the genes which play key roles in the pathways that repair PUFA-induced damage might modify the effect of these FA on colorectal cancer.…”
Section: Polymorphismsmentioning
confidence: 99%
“…This study did not report clinical outcomes. Recently, the results of three further studies with parenteral fish oil administration have become available (51)(52)(53). In the first of these, patients received total parenteral nutrition that included an 8% soybean oil plus 2% fish oil emulsion (controls received a 10% soybean oil emulsion) for 5 days postsurgery (51).…”
Section: Studies Of Fish Oil-containing Parenteral Nutrition In Surgimentioning
confidence: 99%
“…Recently, supplementation with fish oil is supposed to improve standard clinical therapy for chronic hyper-inflammatory diseases such as Crohn' disease [1,5] , rheumatoid arthritis [6] , cancer cachexia [7,8] , and as an adjunct therapeutic measure for trauma, injure, and sepsis [2,[9][10][11][12] . Although several studies have demonstrated the beneficial effects of omega-3 fatty acid supplementation on patient outcome or immune competence, randomized controlled clinical trials focusing on the use of parenteral fish oil are scarce [13][14][15][16][17] . The aim of this study was to assess whether parenteral supplementation of omega-3 fatty acid postoperatively improves the inflammatory and immunological function of colorectal cancer patients and their clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%